1962
DOI: 10.2307/2439693
|View full text |Cite
|
Sign up to set email alerts
|

Cercidium Floridum Seed Coat, Light and Electron Microscopic Study

Abstract: Scott, Flora Murray, B. G. Bystrom, and E. Bowler. (U. California, Los Angeles.) Cercidium floridum seed coat, light and electron microscopic study. Amer. Jour. Bot. 49(8): 821–833. Illus. 1962.—The structure of the seed coat of the desert tree Cercidium is typical of the family Leguminosae, but the inner integument is mucilaginous. The characteristic palisade cells of the epidermis and the many‐armed cells of the mucilaginous zone are discussed in detail. The minute wax rodlets on the surface of the young see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…M. alba; Hamly, 1932Hamly, , 1935. It was also suggested that the light line is a region where the microfibrils changed from a longitudinal to a transverse orientation (Scott et al, 1962;Werker, 1980/81) but this was not the case in soybean (Fig. 10J).…”
Section: Light Linementioning
confidence: 97%
“…M. alba; Hamly, 1932Hamly, , 1935. It was also suggested that the light line is a region where the microfibrils changed from a longitudinal to a transverse orientation (Scott et al, 1962;Werker, 1980/81) but this was not the case in soybean (Fig. 10J).…”
Section: Light Linementioning
confidence: 97%
“…There is obviously another kind of amorphous substance forming the light line. Other SEM descriptions concerning changes in the anticlinal direction of the cell wall fibrils (Scott et al, 1962 [15] ) or differences between more or less thick parts of the cell wall (Manning and Van Staden, 1985 [8] ) cannot be confirmed for the Geraniaceae seed coat.…”
Section: Discussionmentioning
confidence: 89%
“…One amazing feature of the palisade cells in the Geraniaceae is the so-called light line running in a periclinal direction through the secondary cell wall material. The structure and function of the light line, which was so named for its bright character in the light microscope, has been discussed for different plant families, such as the Fabaceae and the Malvaceae (Hamly, 1935 [6] ; Scott et al, 1962 [15] ; Manning and Van Staden, 1985 [8] ; Christiansen and Moore, 1958 [3] ). The light line was often interpreted as an optical phenomenon without any chemical significance (Hamly, 1935 [6] ; Tran and Cavanagh, 1984 [20] ; Rangaswamy and Nandakumar, 1985 [12] ) and was thought to be generated by changes in the fibrillar pattern of the cellulose molecules (Scott et al, 1962 [15] ) or by differences in the cell wall thickness (Manning and Van Staden, 1985 [8] ).…”
Section: Introductionmentioning
confidence: 99%